Synergistic Effect of Colistin with Selected Antibiotic on Colistin Resistant Pseudomonas aeruginosa Strains Isolated from Clinical Samples - Keramati, Zahra; Asadpour, Leila; Habibollahi, Hadi (Novelty in Biomedicine, 2023)
Background: The spread of antibiotic resistance and the emergence of MDR strains, especially in gram-negative bacteria, has led to combining antibiotics to treat infections caused by these bacteria. The study aimed to evaluate some antibiotics' synergistic effect on multidrug-resistant Pseudomonas aeruginosa isolates isolated from clinical samples between thyroid dysfunction and asymptomatic bacteriuria in women of reproductive and postmenopausal age. Materials and Methods: P. aeruginosa was isolated from Rasht city hospitals (North of Iran) clinical specimens with multiple antibiotic resistance. The antibiotic resistance of isolates was determined by the disk diffusion method. The screening checklist evaluated the synergistic effects of ciprofloxacin, colistin, meropenem, and gentamicin. Results: The combination of meropenem and colistin in four isolates was additive, and in two isolates was indifferent. The combined effect of ciprofloxacin and colistin was also incremental in 4 isolates and indifferent in 2 isolates. The combined effect of gentamicin and colistin was indifferent in all selected strains. Conclusion: Results of this study showed that combinations of colistin with ciprofloxacin and colistin with meropenem were successful against resistant isolates, while a combination of gentamicin and colistin showed no synergistic effect. Since the characteristics of each clinical isolate differ from the other isolates, more study with more isolates is recommended to make any precise and definite recommendation.